Designing on-line tunable gain fuzzy sliding mode controller using sliding mode fuzzy algorithm: applied to internal combustion engine - Piltan, Farzin; Sulaiman, Nasri; Talooki, Iraj Asadi; Ferdosali, Payman (IDOSI Publications, 2011)
This paper expands a fuzzy sliding mode based controller which sliding function is on-line tuned by sliding mode fuzzy algorithm. The main goal is to guarantee acceptable trajectories tracking between the internal combustion engine (IC engine) air to fuel ratio and the desired input. The fuzzy controller in proposed fuzzy sliding mode controller is based on Mamdani’s fuzzy inference system (FIS) and it has one input and one output. The input represents the function between sliding function, error and the rate of error. The outputs represent fuel ratio, respectively. The sliding mode fuzzy methodology is on-line tune the sliding function based on self tuning methodology. The performance of the sliding mode fuzzy on-line tune fuzzy sliding mode controller (SFOFSMC) is validated through comparison with previously developed IC engine controller based on sliding mode control theory (SMC). Simulation results signify good performance of fuel ratio in presence of uncertainty and external disturbance.